Foveal processing difficulty does not affect parafoveal preprocessing in young readers - Marx, Christina (Sci Rep, 2017)
Recent evidence suggested that parafoveal preprocessing develops early during reading acquisition, that is, young readers profit from valid parafoveal information and exhibit a resultant preview benefit. For young readers, however, it is unknown whether the processing demands of the currently fixated word modulate the extent to which the upcoming word is parafoveally preprocessed – as it has been postulated (for adult readers) by the foveal load hypothesis. The present study used the novel incremental boundary technique to assess whether 4(th) and 6(th) Graders exhibit an effect of foveal load. Furthermore, we attempted to distinguish the foveal load effect from the spillover effect. These effects are hard to differentiate with respect to the expected pattern of results, but are conceptually different. The foveal load effect is supposed to reflect modulations of the extent of parafoveal preprocessing, whereas the spillover effect reflects the ongoing processing of the previous word whilst the reader’s fixation is already on the next word. The findings revealed that the young readers did not exhibit an effect of foveal load, but a substantial spillover effect. The implications for previous studies with adult readers and for models of eye movement control in reading are discussed.